Pathways to Profits: The Impact of Marketing vs. Finance Skills on Business Performance - Anderson, Stephen J.; Chandy, Rajesh; Zia, Bilal (Management Science, 2018)
This paper examines the impact of improvements in marketing skills relative to finance skills among small-scale entrepreneurs. It addresses three important questions: (1) What is the impact of marketing or finance skills on business profits? (2) How do improvements in marketing and finance skills respectively affect different business outcomes? (3) When are increases in marketing relative to finance skills more beneficial? Through a randomized control study of 852 firms in South Africa, the analysis finds significant improvements in profitability from both types of business skills training. However, the pathways to achieve these gains differ substantially between the two groups. The marketing group achieves greater profits by adopting a growth focus on higher sales, greater investments in stock and materials, and hiring more employees. The finance group achieves similar profit gains but through an efficiency focus on lower costs. Both groups show significantly higher adoption of business practices related to their respective training program. Consistent with a growth focus, marketing/sales skills are significantly more beneficial to businesses run by entrepreneurs with ex ante less exposure to different market contexts. In contrast and in line with an efficiency focus, it is the more established businesses that benefit significantly more from finance/accounting skills. This paper was accepted by Eric Anderson, marketing. Data and the online appendix are available at https://doi.org/10.1287/mnsc.2017.2920 .